Combined pharmacotherapy and evidence-based psychosocial Cannabis treatment for youth and selection of cannabis-using friends. (1st August 2021) - Meisel, Samuel N.; Treloar Padovano, Hayley; Miranda, Robert
Highlights: Time spent with cannabis-using friends promoted greater cannabis use and craving. Youth treated with topiramate pharmacotherapy did not show selection effects. Across conditions, craving and use were unrelated to time with non-using friends. Changing peer affiliations could be one mechanism by which treatments can work. Abstract: Background: Theoretical models of behavior change argue that youth should decrease their time with cannabis-using friends and increase their time with non-using friends during treatment. Informed by behavior-change models of recovery and socialization and selection peer-influence models, the current study examined whether combining evidence-based psychosocial treatment with adjunctive pharmacotherapy helps youth decrease their affiliations with cannabis-using friends and increase their affiliations with non-using friends during cannabis misuse treatment. Methods: Youth ages 15–24 years (51 % male), participated in a double-blind randomized clinical trial that tested the effects of motivational enhancement and cognitive behavioral therapy (MET-CBT) plus topiramate (N = 39) or placebo (N = 26) on cannabis craving and use. Ecological momentary assessment data, collected via smartphones throughout the six-week intervention, assessed youths' time with cannabis-using and non-using friends, cannabis use, and craving in daily life. Multiple group multilevel structural equation modeling tested study hypotheses. Results: Across the topiramate (48 % completion rate) and placebo (77 % completion rate) conditions, greater time spent with cannabis-using friends promoted greater next day cannabis use and craving (socialization effect). In turn, cannabis craving, but not use, promoted continued selection of cannabis-using friends. This indirect effect was only supported in the placebo condition due to the selection piece of this cycle not being significant for youth who received topiramate. Neither cannabis craving nor use were associated with time with non-using friends the next day. Conclusions: MET-CBT and adjunctive topiramate pharmacotherapy interrupted youth selection processes. This finding suggests that changing peer affiliations could be one mechanism by which treatments can work.